PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS BERITA - Putri, Irena Andina; Ratna, Ellya; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
This research aims to describe the influence model of discovery learning by using audiovisual media the skills of news writing. The type of this research is quantitative research done using experimental design. The results of this research are three: (1) news writing skills before using discovery learning model by using audiovisual media are in qualifying Enough (60,76), (2) news writing skills after using discovery learning model by using audiovisual media are in qualification good (80,03), and (3) news writing skills class VIII SMP Negeri 11 Padang after using the model of discovery learning by using audiovisual media better than before using the model of discovery learning by audiovisual media.Â Kata Kunci: pengaruh, discovery learning, audiovisual, berita